2020
DOI: 10.5624/isd.2020.50.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination by radiographic localization of the inferior alveolar canal using cone-beam computed tomography in an Egyptian population

Abstract: Purpose: The purpose of this study was to evaluate possible differences in the location of the inferior alveolar canal in male and female Egyptians. Materials and Methods: This cross-sectional retrospective study involved the evaluation of 210 CBCT scans of Egyptian individuals (18-70 years old). The inferior alveolar canal was localized by measuring 8 linear dimensions: 2 for the vertical localization of the mental foramen (superior and inferior to the mental foramen), 4 at the first molar bifurcation for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
3
2
Order By: Relevance
“…Another study conducted by Angel et al [ 24 ] found that most of the measured distances showed no significant difference between sexes in American population, which is in line with this study. The findings in this study were slightly not in accordance with the studies done by Mirbeigi et al [ 12 ], Balaji et al [ 13 ], Mousa et al [ 19 ], and Nagadia et al [ 25 ] where all the buccal and lingual distances were not statistically significant between both sexes. This difference may be caused by the various ethnicities of patients used in each study as Mirbeigi et al [ 12 ] studied Iranian population, Balaji et al [ 13 ] studied South Indian population, and Mousa et al [ 19 ] studied Egyptian population while Nagadia et al [ 25 ] used Chinese population as their subject samples.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Another study conducted by Angel et al [ 24 ] found that most of the measured distances showed no significant difference between sexes in American population, which is in line with this study. The findings in this study were slightly not in accordance with the studies done by Mirbeigi et al [ 12 ], Balaji et al [ 13 ], Mousa et al [ 19 ], and Nagadia et al [ 25 ] where all the buccal and lingual distances were not statistically significant between both sexes. This difference may be caused by the various ethnicities of patients used in each study as Mirbeigi et al [ 12 ] studied Iranian population, Balaji et al [ 13 ] studied South Indian population, and Mousa et al [ 19 ] studied Egyptian population while Nagadia et al [ 25 ] used Chinese population as their subject samples.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings in this study were slightly not in accordance with the studies done by Mirbeigi et al [ 12 ], Balaji et al [ 13 ], Mousa et al [ 19 ], and Nagadia et al [ 25 ] where all the buccal and lingual distances were not statistically significant between both sexes. This difference may be caused by the various ethnicities of patients used in each study as Mirbeigi et al [ 12 ] studied Iranian population, Balaji et al [ 13 ] studied South Indian population, and Mousa et al [ 19 ] studied Egyptian population while Nagadia et al [ 25 ] used Chinese population as their subject samples. These studies examined different populations, and the variations in genetics, diet, habits, and customs may result in distinct anatomic features [ 26 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This can be attributed to the fact that during male growth, testosterone levels; and the more extended puberty phase, with a related longer duration of bone growth; affected the bone size. Another consideration is the muscular tension that encourages bone growth; because males have stronger masticatory muscles than females, the mandible is generally more developed in males [30,31].…”
Section: Discussionmentioning
confidence: 99%